Protein-based therapeutic for anemia caused by dyserythropoiesis. (1st November 2016) - Arlet, Jean-Benoît; Guillem, Flavia; Lamarque, Mathilde; Dussiot, Michael; Maciel, Thiago; Moura, Ivan; Hermine, Olivier; Courtois, Geneviève
ABSTRACT: Introduction : Major advances have been recently made in understanding the molecular determinants of dyserythropoiesis, particularly due to recent works in β-thalassemia. The purpose of this review is devoted to underline the role of some proteins recently evidenced in the field, that may be new alternative therapeutic targets in the near future to alleviate different types of anemia. Areas covered : This review covers the contemporary aspects of some proteins involved in various types of dyserythropoiesis, including the transcriptional factor GATA-1 and its protective chaperone HSP70, but also cytokines of the transforming growth factor beta (TFG-β) family, TGF-β1 and GDF-11, and hormones as erythroferrone. It will be not exhaustive, but based on major recent published works from the literature in the past three years. Expert commentary : Sotatercept and lustatercept, two activin receptor II ligand traps that block GDF-11, are candidate drugs providing therapeutic hope in different types of ineffective erythropoiesis, including myelodysplastic syndromes (MDS) and β-thalassemia. Furthermore, a new concept emerges to consider erythroid lineage in the bone marrow as an endocrine gland.